2022
DOI: 10.1038/s41420-022-01076-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel mRNA decay inhibitor abolishes pathophysiological cellular transition

Abstract: In cells, mRNA synthesis and decay are influenced by each other, and their balance is altered by either external or internal cues, resulting in changes in cell dynamics. We previously reported that it is important that an array of mRNAs that shape a phenotype are degraded before cellular transitions, such as cellular reprogramming and differentiation. In adipogenesis, the interaction between DDX6 and 4E-T had a definitive impact on the pathway in the processing body (PB). We screened a library of α-helix analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We previously found an association between DDX6 and 4ET, which plays a central role in RNA decay in RNA metabolism. 10 Subsequently, we found that RNA decay regulates adipogenic differentiation by inhibiting the intracellular PPI of DDX6 and 4ET using peptidomimetics with a novel cage-like chemical skeleton. 10 Peptides and peptidomimetics, including ours, can elicit useful effects against intracellular PPIs if they can be stably introduced into cells, but cell membrane permeation is a major barrier that limits peptide drugs from reaching the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously found an association between DDX6 and 4ET, which plays a central role in RNA decay in RNA metabolism. 10 Subsequently, we found that RNA decay regulates adipogenic differentiation by inhibiting the intracellular PPI of DDX6 and 4ET using peptidomimetics with a novel cage-like chemical skeleton. 10 Peptides and peptidomimetics, including ours, can elicit useful effects against intracellular PPIs if they can be stably introduced into cells, but cell membrane permeation is a major barrier that limits peptide drugs from reaching the clinic.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Subsequently, we found that RNA decay regulates adipogenic differentiation by inhibiting the intracellular PPI of DDX6 and 4ET using peptidomimetics with a novel cage-like chemical skeleton. 10 Peptides and peptidomimetics, including ours, can elicit useful effects against intracellular PPIs if they can be stably introduced into cells, but cell membrane permeation is a major barrier that limits peptide drugs from reaching the clinic. One example is ALRN-6924, which was developed to inhibit the association of the tumor suppressor p53 with its inhibitory proteins, MDM2 and MDMX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally this would be possible by perturbing specific kinetic steps of gene expression followed by single-cell transcriptomic and proteomic studies, that could provide interesting insights. [81][82][83][84] While small molecules with mRNA degradation inhibition functions are only just starting to be characterized, [85] transcript(s) specific perturbations (e.g., through the use of miRNA sponges [86] ) or inhibitors of nonsense-mediated mRNA decay [87,88] are already available. The implication of blocking transcript-shared mechanisms is perhaps a little less clear.…”
Section: Discussionmentioning
confidence: 99%